2012
DOI: 10.1007/s12028-012-9784-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Efficacy, Pharmacokinetics, and Administration of Intraventricular Vancomycin in Adults

Abstract: Central nervous system infections requiring treatment with intraventricular (IVT) vancomycin are becoming increasingly common with advent of intracranial devices and increasing prevalence of multi-drug resistant and nosocomial organisms. Administering vancomycin via IVT route bypasses the blood-brain barrier to allow localized and controlled delivery directly to the desired site of action, achieving high concentrations for more reliable bactericidal action. This article systematically reviews current literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 29 publications
0
53
0
3
Order By: Relevance
“…Although there are methodological limitations in published studies, intraventricular vancomycin was shown to be safe and efficacious in a systematic review in adults [124]. Intraventricular aminoglycosides were also shown to be effective [122,126].…”
Section: Evidence Summarymentioning
confidence: 98%
“…Although there are methodological limitations in published studies, intraventricular vancomycin was shown to be safe and efficacious in a systematic review in adults [124]. Intraventricular aminoglycosides were also shown to be effective [122,126].…”
Section: Evidence Summarymentioning
confidence: 98%
“…Consequently intraventricular vancomycin, either added if patients are unresponsive or at an initial diagnosis, is commonly used. 26 A dose of 5e20 mg/day administered by the intraventricular route results in mean trough CSF vancomycin levels of 81 mg/L with minimal, if any, adverse effects. 26 The intraventricular route is frequently used for treatment but not every centre monitors CSF levels.…”
Section: Treatmentmentioning
confidence: 99%
“…26 A dose of 5e20 mg/day administered by the intraventricular route results in mean trough CSF vancomycin levels of 81 mg/L with minimal, if any, adverse effects. 26 The intraventricular route is frequently used for treatment but not every centre monitors CSF levels. However, there is insufficient evidence to support the use of prophylactic intraventricular vancomycin when inserting EVDs or VP shunts.…”
Section: Treatmentmentioning
confidence: 99%
“…Further, it is proved by fluorescence microscopy studies that FITC-D3 accumulates in the vacuolar compartments of the cells and can be detected in various structures and populations of cells after injection into the brain. Similarly, convection-enhanced delivery into the putamen nucleus [70], PDA, pressure support, surfactant therapy, inotropic drug administration, vaginal delivery, neonatal resuscitation, and antenatal corticosteroid therapy could be more significantly used higher in cases with IVH (intraventricular hemorrhage) [71]. It is mainly used to treat hyaline membrane disease and preeclampsia in mother [60].…”
Section: Cns Protectionmentioning
confidence: 99%